Challenges of disinfection by-products in water and effect on the men's health infertility- A Narrative review - R,Kalankesh, Laleh; Kheirandish, Reza; Nematollahi, Shahrzad; Hosseini, Jalil; Esmailli, Maedeh; Aliakbari, Fereshteh (Archives of Men's Health, 2020)
Chlorination is the most common disinfectant in the water treatment process. The reaction between Natural Organic Matter (NOM) in water and chlorine lead to the formation of harmful disinfectant by-products (DBPs). The most common DBPs (HAAs and THMs) impose risks on human health. The data acquired from human samples on the relationship of men's infertility with DBPs exposure are limited and epidemiological studies have reported various results about the association between long-term exposure to DBPs and the adverse effect on the man's infertility (sperm concentration, semen quality and sperm motility). Previous cellular studies show that HAAs and THM damaged DNA by their effect on the ROS generation and Oxidative stress, respectively. Moreover, CDBM can lead to decreased litter sizes and pup viability. Bromodichloromethane (BDCM) cause the production of sperm abnormalities. In addition, Trichloromethane (TCM) led to increase the degeneration of epididymis ductal epithelium. Dibromoacetic acid (DBAA) and Bromochloroacetic acid (BCAA) led to synergistical decrease in the levels of SP22 sperm membrane protein. Likewise, BCAA and DBAA resulted in testicular damage. It should be noted that synergistic effect between Br THMs and TCAA in relation to below-reference sperm count was demonstrated. It has been reported that mixture of THMs and HAAs lead to increase sperm motility in adult male rats.